FAKTOR - FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KOPI ANGKRINGAN JALAN SUROMENGGOLO PONOROGO - Samodro Kristi Utomo; Rochmat Aldi Purnomo; Yeni Cahyono (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
The purpose of this study was to examine the effect of length of business, capital and trading location on traders' income partially or simultaneously. The population in this study were the coffee traders on Jalan Suromenggolo, Ponorogo. The sampling technique used by the researcher is the saturated sampling method, totaling 55 traders. The data taken to conduct this research is primary data using a questionnaire instrument. Testing the analysis of data quality used validity and reliability tests. Then to test the hypothesis using the partial regression coefficient test (t test), the simultaneous significance test, and the determinant coefficient. The data analysis method used is multiple linear regression. The results of this study indicate that partially the length of business has a positive and significant effect on the income of traders, business capital has a significant effect on the income of traders, and the location of the business has a significant effect on the income of traders. Simultaneously shows that the length of business, business capital, and business location simultaneously affect the income of traders